2015
DOI: 10.1158/2159-8290.cd-15-0116
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ETV1 in Gastrointestinal Stromal Tumors: Tripping the Circuit Breaker in GIST?

Abstract: Summary: Activating mutations in the KIT or PDGFRA receptor tyrosine kinase genes are the key oncogenic drivers in the majority of gastrointestinal stromal tumors (GIST), but novel results now show that aberrant kinase signaling is potentiated by a positive feedback circuit that involves the ETS transcription factor ETV1. Targeting ETV1 can disrupt this circuit and represents a promising new therapeutic approach for the treatment of GISTs.See related article by Ran and colleagues, p. 304 (5).Gastrointestinal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…These studies demonstrate that both KIT-dependent and -independent pathways are active in some cases of GIST and these patients may not respond to KIT inhibition alone. Recent studies have shown that transcription factor ETV1 activates a positive feedback mechanism for KIT transcription and its levels are maintained by MAPK signaling pathway and PDGFRA signaling in KIT-mutant GIST (21,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrate that both KIT-dependent and -independent pathways are active in some cases of GIST and these patients may not respond to KIT inhibition alone. Recent studies have shown that transcription factor ETV1 activates a positive feedback mechanism for KIT transcription and its levels are maintained by MAPK signaling pathway and PDGFRA signaling in KIT-mutant GIST (21,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Such discoveries facilitate the identification of novel therapeutic and chemoprevention agents, and classification of patients into molecular subgroups to personalise therapy. For example, it allows for the repositioning of ETV1 inhibitors, one of which has been employed in a clinical trial for gastrointestinal stromal tumours28,39.…”
mentioning
confidence: 99%
“…Te ETV1-c-KIT signaling is the key positive feedback to promote GIST progression [19]. Our study reveals that ADRB2 is essential for ETV1-c-KIT feedback in GISTs.…”
Section: Discussionmentioning
confidence: 64%
“…We further explored the molecular mechanism of ADRB2 signalingmediated efects. ETV1-c-KIT signaling is a key positive feedback to promote GIST progression [19]. In ADRB2overexpressing GIST cells, ETV1, c-KIT, and p-ERK(Y204) expression were increased (Figure 5(a)).…”
Section: Adrb2 Enhances the Etv1-c-kit Signalingmentioning
confidence: 99%